Wybrane problemy finansowania działalności związków wzajemności członkowskiej - Janowicz-Lomott, Marietta (Select Problems of Members Unions' Financial Acitivity, 2008)
The paper briefly characterizes selected financial problems of groups of policyholders (members unions) separated within mutual insurance company. In the article, the author describes: - different solutions of members unions' participating in insurer's operating expenses, - various technical reserves that mutual insurer is required to maintain by law and justification which of them are important for members unions, - methods of calculating and presenting members unions' financial statements and refunding surplus. The author proposes some solutions for Polish insurance law, contracts between a mutual insurer and its members unions and accounting practise, which are important for members unions' development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 88-96